Eco-sustainable design of humic acids-doped ZnO nanoparticles for UVA/light photocatalytic degradation of LLDPE and PLA plastics. Issue 1 (February 2023) - Amato, Paola; Muscetta, Marica; Venezia, Virginia; Cocca, Mariacristina; Gentile, Gennaro; Castaldo, Rachele; Marotta, Raffaele; Vitiello, Giuseppe
Abstract: The mismanagement of plastics is associated with high levels of waste and release into the environment, where they can persist for long times due to the low degradation rate. Photocatalytic methods, based on the action of Reactive Oxygen Species (ROS) generated by semiconductor materials, are promising eco-friendly and low-cost process for the plastics degradation. Here, eco-designed Humic Acids-doped/ZnO nanoparticles were synthesized via solvothermal route and tested as photocatalysts for the degradation of linear low-density polyethylene (LLDPE) and polylactic acid (PLA) thin films, under UVA/light irradiation. LLDPE is one of the most common commercial polymers widely used in packaging field wherein PLA is also broadly used to replace conventional plastics. The combination of analytical techniques allowed to define the structure-property-function relationships of the hybrid nanomaterials and to monitor the chemical, structural and morphological changes occurring on the polymeric films as a consequence of the photodegradation. Experimental results demonstrated the validity of this eco-sustainable approach to realize hybrid photocatalysts with enhanced ROS-generating ability suitable for an improved photo-oxidation of plastics in aqueous environment. Graphical Abstract: ga1 Highlights: A bottom-up solvothermal synthesis leads to humic acid-doped ZnO nanoparticles. The supramolecular design of nanohybrids valorizes the biowaste-derived molecules. An improved ROS-generating ability occurs in aqueous medium under UVA irradiation. Humic acid-doped ZnO nanoparticles enhance the photo-oxidation of LLDPE and PLA films. Photodegradation results in deep furrows on the surface of plastic films.